DIVERSIFIKASI OLAHAN SALAK UNTUK MENINGKATKAN KEMANDIRIAN DAN KUALITAS HIDUP MASYARAKAT DESA PURWOBINANGUN - M., Miftahudduha; Rahayu, Mugi; Purnamasari, Kadek Intan Putri; Amrizal, Fandinata; Junaedi, Hardi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Snake fruit is a kind of fruit that can be harvested all year long, although theres a time in a year when the trees produces an extra ordinarily huge amount of fruits, or as local people say it panen raya, literally means great harvesting. The price for every kilo of snake fruits dropped drastically when panen raya comes. Salak pondoh (local name for Purwobinanguns snake fruit) are normally priced about Rp 8.000,00 - Rp 12.000,00 per kilo when they are not in season and about Rp 2.000,00 - Rp 5.000,00 when its time for panen raya. It means snake fruits farmers suffer a substantial amount of financial loss.